From Anthropology: Understanding Public Health in the Salvadoran Context (Raíces: Revista de Ciencias Sociales y Políticas, 2021)
Health has had various conceptualizations in different coordinates, and this has allowed reasonable actions based on the construction of the concept, in some communities there has been talk of supernatural diseases, on the other hand, in States such as El Salvador in the 19th century, diseases had a rationalization of health, being necessary to ask from anthropology What is health? How does the concept of health intervene in the configuration of society and minority groups? Precisely in understanding these questions about cultural systems, a social difference emerges when addressing the health problem, it is therefore relevant in the context of a pandemic where it is feasible to question public health decisions.
Keywords: Culture; Health; Concept; Society; El Salvador